1/6(8x-13)-2/3=5/6(x+2)

Simple and best practice solution for 1/6(8x-13)-2/3=5/6(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/6(8x-13)-2/3=5/6(x+2) equation:


x in (-oo:+oo)

(1/6)*(8*x-13)-(2/3) = (5/6)*(x+2) // - (5/6)*(x+2)

(1/6)*(8*x-13)-((5/6)*(x+2))-(2/3) = 0

(1/6)*(8*x-13)+(-5/6)*(x+2)-2/3 = 0

1/6*(8*x-13)-5/6*(x+2)-2/3 = 0

(1/6*3*(8*x-13))/3+(-5/6*3*(x+2))/3-2/3 = 0

1/6*3*(8*x-13)-5/6*3*(x+2)-2 = 0

3/2*x-23/2-2 = 0

3/2*x-27/2 = 0

(3/2*x-27/2)/3 = 0

(3/2*x-27/2)/3 = 0 // * 3

3/2*x-27/2 = 0

3/2*x-27/2 = 0 // + 27/2

3/2*x = 27/2 // : 3/2

x = 27/2/3/2

x = 9

x = 9

See similar equations:

| 5y+30=3+4y | | z-0.013=-6.360 | | 8x-4=19+5 | | 6=10-(3/7y) | | 4s-3(2s+2)=6 | | B-20=4r | | 14+x=120 | | 4=xy+2x | | -11=k-20 | | 15x-45=-30x+45 | | (x/3)-(1/2)=(x/6) | | -3(r+9)=-52 | | 4.91-10.27w=4.11w+17.56 | | 3(2y-6)=4y-7 | | B=f-r/z | | a=20-2x | | 8x+6-5x=2x-3 | | 1/6x+2/3-2/15=4/3x+1/5 | | 6x+11=180 | | z+(3.19)=5.83 | | 5(2y-6)=4y-7 | | 4g+3h+g+2h= | | 6+a= | | Y=5x(4) | | 2-4x=5x-16 | | -4x+8=4(2x-2)-2(-16+8x) | | 2A+B^2=4 | | 8n-(5n+4)=8 | | W/11=W+24/3 | | -52+x=-2x+20 | | 4/7x=200 | | 3x+2x=5(x+10) |

Equations solver categories